A biblioteca escolar na rede pública estadual de ensino: entre o real e o ideal - GONÇALVES, Benedita do Socorro da Silva (2017)
It presents concepts of a school library and the resources considered necessary for the acting of this pedagogical space within the educational institutions, furthermore, it exposes how the Brazilian legislation supports legally the existence of a library within educational institutions, and also what are the recommended minimum parameters for the functioning of this pedagogical space. Its general objective is to develop a study on school libraries of the Public State Education Network of the State of Pará, to better clarify their roles in the educational context and, as specific objectives, to explore concepts of school libra ry recognized in the literature; Present the situational picture of a certain sampling, represented by two school libraries of the educational network in question, besides analyzing if the studied information units fulfill their role of school library. For that, an exploratory research was carried out, which involved bibliographical, documentary and case study research. With the condition that for the data collection during the case study was accomplished observation and application of questionnaire with qualitative approach. From the analysis of the data, it was concluded that the resources available to the school libraries, such as: infrastructure, informational, human and financial resources, are not sufficient to support the teaching-learning of the students, what can certainly prejudice their intellectual and social progression.